The novel inhaled dual PDE3 and PDE4 inhibitor ensifentrine for the treatment of COPD: A systematic review and meta-analysis protocol on trough FEV1 and exacerbation according to PRISMA statement - Luigino Calzetta; Mario Cazzola; Shima Gholamalishahi; Paola Rogliani (Current Research in Pharmacology and Drug Discovery)
The investigation of ensifentrine, an inhaled dual phosphodiesterase (PDE)3 and PDE4 inhibitor, for chronic obstructive pulmonary disease (COPD) maintenance therapy presents a significant clinical interest. Despite promising results from recent Phase III trials, a comprehensive synthesis of its therapeutic efficacy in COPD is lacking. This protocol outlines the first registered systematic review and meta-analysis in PROSPERO to assess the impact of ensifentrine on trough forced expiratory volume in the 1st second (FEV1) and acute exacerbations of COPD. By conducting a rigorous literature search and employing solid methodologies, this endeavour aims to provide robust evidence on the real efficacy of ensifentrine. Anticipated outcomes include a significant improvement in trough FEV1 and a reduction in AECOPD risk among ensifentrine-treated patients compared to controls, corroborating its bronchodilator and anti-inflammatory properties. The meta-analysis expects to reveal consistent results across different trials, enhancing confidence in the findings. Additionally, subgroup analyses may unveil factors influencing the efficacy of ensifentrine, guiding optimal therapeutic strategies. Overall, this protocol holds the potential to inform clinical practice and regulatory decisions, positioning ensifentrine as a valuable addition to COPD management.